Functionality in elderly people with COPD, face-to-face rehabilitation and telerehabilitation: A systematic review - Yáñez-Yáñez, Rodrigo; Mc Ardle-Draguicevic, Nelson; Martínez-Alarcón , Carolina; Quintana-Peña , Pedro (Horizonte Sanitario, 2022)
Objective: To synthesize the existing evidence on the main results of face-to-face and/or telerehabilitation rehabilitation programs on functionality in elderly people with COPD.Materials and method: We searched for scientific articles in the following databases: Medline via PubMed and BVS Lilacs that met the eligibility criteria, between January 1, 2019 and January 1, 2021, selecting 4 documents. The keywords "Aged", "Pulmonary Disease, Chronic Obstructive", "Rehabilitation - Telerehabilitation" were used to identify articles.Results: The average age of the participants was 65.4, male studies predominated and of the elderly included with COPD, 50% suffered from severe COPD. Regarding the description of the rehabilitation programs, 75% had follow-up of the results, from 3 to 12 months, 50% of the programs had a duration of 10 weeks, in 50% of the cases the patients were provided with technology for home use and only 15% used a mobile application.Conclusion: The results support the view that health care providers can use telerehabilitation for the treatment of older persons with COPD in conjunction with usual rehabilitation.Keywords: Aged; Telerehabilitation; Chronic obstructive pulmonary disease; Systematic Review